A facile hydrothermal synthesis of carbon dots modified g-C3N4 for enhanced photocatalytic H2-evolution performance. Issue 19 (4th May 2017) - Wang, Xuefei; Cheng, Jingjing; Yu, Huogen; Yu, Jiaguo
Abstract : A facile strategy to realize the homogeneous and solid modification of carbon dots on the g-C3 N4 surface. Abstract : Carbon dots (CDs)/g-C3 N4 is a promising photocatalyst to split water for H2 production; however, the synthesis of CDs/g-C3 N4 is usually rigorous and involves multiple steps, which limits its practical application. In this study, a facile hydrothermal approach was developed to prepare CDs/g-C3 N4 photocatalysts usingl -ascorbic acid and g-C3 N4 as the precursors. Upon in situ thermal polymerization ofl -ascorbic acid on the g-C3 N4 surface, the carbon dots were homogeneously and solidly modified on the g-C3 N4 surface. The CDs/g-C3 N4 photocatalysts showed higher photocatalytic performance for H2 production than g-C3 N4 under UV light irradiation using lactic acid as the sacrificial agent. The improved photocatalytic performance of CDs/g-C3 N4 was mainly attributed to rapid interfacial charge transfer. After a Pt co-catalyst was loaded, the Pt-CDs/g-C3 N4 catalyst formed exhibited a further improved photocatalytic performance for H2 production and could even split pure water to produce H2 . Considering our present economic and facile synthetic approach for the modification of carbon dots on the surface of g-C3 N4 photocatalysts, the as-prepared CDs/g-C3 N4 photocatalysts will be promising for practical use in water splitting.